Double zero-tillage and foliar-P nutrition coupled with bio-inoculants enhance physiological photosynthetic characteristics and resilience to nutritional and environmental stresses in maize–wheat rotation - Harish, M. N.; Choudhary, Anil K.; Bhupenchandra, Ingudam; Dass, Anchal; Rajanna, G. A.; Singh, Vinod K.; Bana, R. S.; Varatharajan, T.; Verma, Parkash; George, Saju; Kashinath, G. T.; Bhavya, M.; et al. (Frontiers in Plant Science, 2022)
Conventionally tilled maize–wheat is an emerging cereal production system in the Indo-Gangetic Plains Region (IGPR) of south-Asia, involving excessive tillage operations that result in low productivity and numerous resource- and environmental-stresses. At the same time, phosphorus (P) is a vital nutrient that limits crop growth and development, and ~80% of Indian soils are low to medium in available-P due to its sparing solubility again resulting in crop stress and low yields in this system. Hence, crop productivity, photosynthetic parameters and resilience to nutritional and environmental stresses were assessed under a maize-wheat cropping system (MWCS) using four crop-establishment and tillage management practices [FBCT-FBCT (Flat bed-conventional tillage both in maize and wheat); RBCT-RBZT (Raised bed-CT in maize and raised bed-zero tillage in wheat); FBZT-FBZT (FBZT both in maize and wheat); PRBZT-PRBZT (Permanent raised bed-ZT both in maize and wheat], and five P-fertilization practices [P100 (100% soil applied-P); P50+2FSP (50% soil applied-P + 2 foliar-sprays of P through 2% DAP both in maize and wheat); P50+PSB+AM-fungi; P50+PSB+AMF+2FSP; and P0 (100% NK with no-P)] in split-plot design replicated-thrice. The results indicated that double zero-tilled PRBZT–PRBZT system significantly enhanced the grain yield (6.1; 5.4 t ha-1), net photosynthetic rate (Pn) (41.68; 23.33 μ mol CO2 m-2 sec-1), stomatal conductance (SC) (0.44; 0.26 mol H2O m-2 sec-1), relative water content (RWC) (83.3; 77.8 %) and radiation-use efficiency (RUE) (2.9; 2.36 g MJ-1) by 12.8–15.8% and 8.5–44.4% in maize and wheat over conventional tilled FBCT–FBCT, respectively. P50+PSB+AMF+2FSP, conjugating soil applied-P, microbial-inoculants and foliar-P, had significantly higher Pn, SC, RUE and RWC over P100 besides saving 34.7% fertilizer-P under MWCS. P50+PSB+AMF+2FSP practice also had higher NDVI, PAR, transpiration efficiency and PHI over P100 due to sustained and synchronized P-bioavailability.